Upaya Pengelola Melalui Program Pohon Geulis Dalam Meningkatkan Minat Baca Peserta Didik Program Kesetaraan Paket C - Deti Nudiati; Lena Miranti Anggraeni (Jayapangus Press, 2023)
The change that non-formal education wants to achieve in community development is the growth of a learning society. One of the characteristics of a learning society is the formation of a reading society. The initial stage towards readability is reading interest. This research was conducted at PKBM Bhina Swakarya, Batujajar District, West Bandung Regency. The purpose of this study was to determine the interest in reading at PKBM Bhina Swakarya and the manager's efforts to increase reading interest in his institution. This study used qualitative descriptive method. The informants in this study amounted to 5 people, the selection of informants used data source sampling techniques with certain considerations. The data collection techniques used in this study used interview, observation, and documentation techniques. The results of this study obtained that, 1) the initial condition of students carrying out reading activities for five minutes, 2) efforts made by the manager to increase interest in reading by making interesting programs, making visits to reading parks, assigning students to read, summarize, and make interesting summary results, 3) It was found that there was an increase in reading interest after the “pohon geulis” program which was a form of management effort to increase the reading interest of students of the high school equivalence education program. The increase in reading interest occurs because the obligation of students to read is imitated from the aspects of time spent, reading frequency, and quantity of reading. The increase in reading interest is due to the implications of the implementation of the “pohon geulis” in terms of student curiosity, the need for information, and the principle of students that reading is a necessity.